Comparison of terlipressin plus sclerotherapy with somatostatin plus sclerotherapy to control bleeding from esophageal varices in with Child C cirrhosis patients - Ali HAFTA; Aziz YAZAR; Cengiz PATA (Turkish Journal of Gastroenterology, 2019)
-